2008
DOI: 10.1139/x08-039
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of different secondary successional pathways in an Alaskan boreal forest

Abstract: Postfire succession in the Alaskan boreal forest follows several different pathways, the most common being self-replacement and species-dominance relay. In self-replacement, canopy-dominant tree species replace themselves as the postfire dominants. It implies a relatively unchanging forest composition through time maintained by trees segregated within their respective, ecophysiological niches on an environmentally complex landscape. In contrast, species-dominance relay involves the simultaneous, postfire estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 21 publications
5
59
0
2
Order By: Relevance
“…Canopy openings created through the senescence and death of the early-colonizing broadleaf species result in the establishment or release of more shade-tolerant, slower-growing conifers (Kneeshaw and Bergeron 1996, Bergeron 2000, Brassard and Chen 2006. Self-replacement can also occur, however, in which broadleaf species re-establish themselves in canopy openings through successful root suckering (Bergeron 2000, Cumming et al 2000, Senecal et al 2004, Kurkowski et al 2008.…”
Section: The Role Of Fire In Stand Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Canopy openings created through the senescence and death of the early-colonizing broadleaf species result in the establishment or release of more shade-tolerant, slower-growing conifers (Kneeshaw and Bergeron 1996, Bergeron 2000, Brassard and Chen 2006. Self-replacement can also occur, however, in which broadleaf species re-establish themselves in canopy openings through successful root suckering (Bergeron 2000, Cumming et al 2000, Senecal et al 2004, Kurkowski et al 2008.…”
Section: The Role Of Fire In Stand Initiationmentioning
confidence: 99%
“…Given the complex interacting effects of disturbance (including type, size, frequency and intensity), seed and bud source availability, seed dispersal, seedbed quality, competition, climatic, edaphic and topographic variability, insect pests, fungal pathogens and herbivory, it is not surprising that mixedwood boreal forests display a wide variety of pathways (Cattelino et al 1979, Bergeron and Dubuc 1989, Caners and Kenkel 2003, Kurkowski et al 2008, Taylor and Chen 2011. Throughout the boreal mixedwood, there is considerable variation on the "classical" mixedwood forest dynamic model (Chen and Popadiouk 2002).…”
Section: Patterns Of Mixedwood Stand Dynamicsmentioning
confidence: 99%
“…Relay floristics therefore extend post-fire trends in albedo and transpiration for many decades, whereas conifer self-replacement expedites the return to pre-fire conditions. While studies have demonstrated that pre-fire forest age and composition, fire severity, climate, topography, aspect, and initial tree recruitment influence tree successional pathway (Mann and Plug, 1999;De Grandpré et al, 2000;Fastie et al, 2003;Johnstone and Kasischke, 2006;Johnstone and Chapin III, 2006;Kurkowski et al, 2008;Johnstone et al, 2010b;, the prevalence of these across North America remains largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Ring counts from pre-fire stands indicated most stands were approximately 100-150 years old when they burned in the 1998 fire, with a small number of trees or stands aging up to 250 years. Chronosequence and height-growth analyses suggest that boreal mixedwood stands require ;100-200 years of succession for white spruce to replace aspen in the forest canopy (Bergeron 2000, Kurkowski et al 2008, Strong 2009). If aspen had been abundant in post-fire stands during the previous fire free interval, we would expect to have seen a large portion of our sites showing evidence of aspen in the pre-fire stands.…”
mentioning
confidence: 99%